Clinical Indications for Advanced Scleral Lenses (Canadian Eye Care Today, 2023)
The origins of scleral lenses date back to the early 20th century when ground glass was used to manufacture scleral shells to improve vision, and to protect and support the ocular surface. More than 120 years later, current scleral lenses are used for the same general purposes of sight restoration and ocular surface rehabilitation. Today’s scleral lenses are made of highly breathable polymers allowing them to be worn successfully for multiple hours in a day. Furthermore, our access to sophisticated technology allows for the production of highly customized and reproducible lenses.